2008
DOI: 10.1038/sj.sc.3102171
|View full text |Cite
|
Sign up to set email alerts
|

Serum leptin, abdominal obesity and the metabolic syndrome in individuals with chronic spinal cord injury

Abstract: Study Design: Cross-sectional comparison. Objective: The mortality rate is higher in individuals with spinal cord injury (SCI), and one major cause is cardiovascular disease (CVD). In the general population, the metabolic syndrome (MetS) is associated with an increased risk of CVD, and abdominal obesity is a major feature. Adipokines, secreted by adipose tissue, contribute to obesity-linked metabolic diseases. The aim of this study is to evaluate the prevalence of MetS, the components of this syndrome, especia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
99
2
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(110 citation statements)
references
References 20 publications
(16 reference statements)
3
99
2
6
Order By: Relevance
“…Although BMI seems to be a poor representative marker for obesity in SCI population, 14 still the existence of a strong correlation between BMI and fat mass allows the mentioned comparison between Maıïmoun and Huang results. However a positive association with plasma leptin level and BMI has been frequently reported in patients with SCI 9,20 which is in line with our outcomes. By considering this fact that body composition after spinal cord injury undergoes some massive changes 21,22 including decreased total lean mass along with increased total fat mass and visceral fat area, the higher level of leptin in SCI patients was justified ( Table 3).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Although BMI seems to be a poor representative marker for obesity in SCI population, 14 still the existence of a strong correlation between BMI and fat mass allows the mentioned comparison between Maıïmoun and Huang results. However a positive association with plasma leptin level and BMI has been frequently reported in patients with SCI 9,20 which is in line with our outcomes. By considering this fact that body composition after spinal cord injury undergoes some massive changes 21,22 including decreased total lean mass along with increased total fat mass and visceral fat area, the higher level of leptin in SCI patients was justified ( Table 3).…”
Section: Discussionsupporting
confidence: 82%
“…Huang et al 9 reported that although leptin concentration is higher in patients with SCI than control group with matched BMI, body mass index was positively related with leptin level in both groups separately which is in line with Maïmoun results. Maruyama and et al 20 also showed that total lean mass is decreased in spinal cord injured patients along with increased total fat mass and visceral fat area. Although BMI seems to be a poor representative marker for obesity in SCI population, 14 still the existence of a strong correlation between BMI and fat mass allows the mentioned comparison between Maıïmoun and Huang results.…”
Section: Discussionmentioning
confidence: 93%
“…This is important because liver pathology, including inflammation and fatty infiltration, is associated with metabolic syndrome, which occurs at increased incidence in the SCI population. [7][8][9] Indeed, SCI patients commonly have many features of metabolic syndrome, including insulin resistance, increased abdominal adiposity, altered cholesterol levels, and abnormal metabolic hormone levels. 8,10,11 In fact, one study reported evidence of metabolic syndrome in 43% of persons with SCI examined.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Indeed, SCI patients commonly have many features of metabolic syndrome, including insulin resistance, increased abdominal adiposity, altered cholesterol levels, and abnormal metabolic hormone levels. 8,10,11 In fact, one study reported evidence of metabolic syndrome in 43% of persons with SCI examined. 8 The occurrence of metabolic syndrome and its hepatic manifestation termed nonalcoholic fatty liver disease (NAFLD) predict future cardiovascular disease, morbidity, and mortality, contusion injury after which clinical markers of liver pathology were assessed, including hepatic lipid accumulation, macrophage activation, cytokine expression, and serum levels of alanine transaminase (ALT).…”
Section: Introductionmentioning
confidence: 99%
“…10 For studies that have reported both BMI and % BF, an average BMI of 25 kg/m 2 (considered normal weight in able-bodied populations) usually translates to >30%BF in persons with SCI. [11][12][13][14][15][16][17][18][19][20][21] To put this in perspective, one study reported that persons with SCI are ∼13% fatter than age, height and ethnicity-matched able-bodied controls at the same BMI. 19 In fact, recent recommendations are to consider people with chronic SCI and BMI values >22 kg/m 2 as being at high risk for obesity and obesity-related chronic diseases.…”
mentioning
confidence: 99%